Multichannel Coding of Applause Signals. (30th August 2007) - Hotho Hotho, Gerard Gerard; Par Par, Steven van de Steven van de; Breebaart Breebaart, Jeroen Jeroen
Abstract : We develop a parametric multichannel audio codec dedicated to coding signals consisting of a dense series of transient-type events. These signals of which applause is a typical example are known to be problematic for such audio codecs. The codec design is based on preservation of both timbre and transient-type event density. It combines a very low complexity and a low parameter bit rate (0.2 kbps). In a formal listening test, we compared the proposed codec to the recently standardised MPEG Surround multichannel codec, with an associated parameter bit rate of 9 kbps. We found the new codec to have a significantly higher audio quality than the MPEG Surround codec for the two multichannel applause signals under test. Though this seems promising, the technique presented is not fully mature, for example, because issues related to integration of the proposed codec in the MPEG Surround codec were not addressed.